Myths, lies, and downright stupidity : get out the shovel-- why everything you know is wrong - Stossel, John. (New York : Hyperion, 2006)
Myths and misconceptions covered in the book include: Is the media unbiased? Are our schools helping or hurting our kids? Do singles have a better sex life than married people? Do we have less free time than we used to? Is outsourcing bad for American workers? Suburban sprawl is ruining America; money makes people happier; the world is too crowded; we$1 (Bre drowning in garbage; profiteering is evil; sweatshops exploit people. Investigative reporter Stossel takes on these issues and many more.--From publisher description.s
Clueless media -- He and she -- Bashing business -- Monster government -- Stupid schools -- Consumer cons -- The lawsuit racket -- Experts for everything -- The power of belief -- Our health -- Perils of parenting -- The pursuit of happiness.
Includes bibliographical references (p. [285]-296) and index.
Keywords: Common fallacies -- United States; Quality of life -- United States; Social problems -- United States